Transforming food environments: a global lens on challenges and opportunities for achieving healthy and sustainable diets for all - Goh, Ee Von; Sobratee-Fajurally, Nafiisa; Allegretti, Antonio; Sardeshpande, Mallika; Mustafa, Maysoun; Azam-Ali, Susan Helen; Omari, Rose; Schott, Johanna; Chimonyo, Vimbayi Grace Petrova; Weible, Daniela; Mutalemwa, George; Mabhaudhi, Tafadzwanashe; et al. (Frontiers in Sustainable Food Systems, 2024)
Food environments are rapidly changing globally, both in developed and developing contexts, contributing to poor dietary habits and environmental concerns. As a result, more than 80% of countries in the world face different forms of malnutrition, while the environment faces further degradation due to unsustainable production and consumption patterns. Understanding food environments in diverse settings via a global lens is critical for facilitating the global transition to sustainable and healthy food environments.A virtual workshop was held with stakeholders from five nations (Germany, Ghana, Malaysia, South Africa, and Tanzania) representing varying levels of development to interrogate global food environment concerns and propose cross cutting thematic areas that may be explored and addressed through policy change and intervention. The workshop initiated a transdisciplinary project to shape food environments for sustainable and healthy diets. The Reference Manual for Convenors of Food Systems Summit Dialogues for United Nations Food Systems Summit (UNFSS) (United Nations, 2020) was used as guidance to ensure that an inclusive mix of stakeholders were invited. The stakeholders included key players from public and private sectors in disciplines of agriculture, agroforestry, environment and ecology, education, food retail and market, trade and commerce, health care and nutrition. Following the workshop discussion, the findings were analyzed using a general inductive approach. Through triangulation of findings, we identified the common challenges and opportunities for achieving collective nutritional, social and environmental sustainability in the modern food environments, which have become more universal globally. It is evident that research and data are essential for sustainable development of food systems, while Sustainable Development Goal (SDG) 17 -Partnership for the Goals -should be placed at the core of the transformative process. We proposed several research-driven transdisciplinary interventions to facilitate a paradigm shift from the profit logic model over everything else, and to counter the existing policy fragmentation and systemic challenges to making food environments nutrition-sensitive and socially and environmentally sustainable.